ChemInform Abstract: Facile Synthesis and Stereo‐Resolution of Chiral 1, 2, 3‐Triazoles. Issue 37 (September 2015) - Shi, Ye; Ye, Xiaohan; Gu, Qiang; Shi, Xiaodong; Song, Zhiguang
Abstract Lipase‐catalyzed kinetic resolution of readily available functionalized triazoles (VI) and (VII) provides enantiomerically pure chiral triazoles, which are successfully applied as ligands in the asymmetric addition of Et2Zn to aromatic aldehydes (IX).